Tantalum carbide coating product and preparation method thereof

The tantalum carbide coating is prepared on the surface of the substrate by chemical vapor deposition method, which solves the problems of difficulty in deposition of tantalum carbide coating products on the surface of non-carbon-based materials in the prior art, and achieves high purity and high binding strength Preparation of tantalum carbide coating, suitable for industrial production.

CN115584486BActive Publication Date: 2025-02-11XIAMEN SINOMA HANGTE TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211247918.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-12
Publication Date
2025-02-11
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

Existing tantalum carbide coating products are prone to cracks during the preparation process, and are difficult to deposit on the surface of non-carbon-based materials, and have high processing costs and poor ductility, making them difficult to widely use.

Method used

A tantalum carbide coating is prepared on the surface of the substrate by using chemical vapor deposition method, and the mixture of tantalum pentachloride or tantalum pentafluoride gas and hydrogen and mixed olefins is deposited at a temperature of 550~750°C.

Benefits of technology

It has achieved the preparation of high-purity, high bonding strength, corrosion-resistant and wear-resistant tantalum carbide coatings on the surface of the substrate, reducing production costs, improving production efficiency, and suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115584486B_ABST
    Figure CN115584486B_ABST
Patent Text Reader

Abstract

The present invention relates to a tantalum carbide coating product and a preparation method, wherein a tantalum carbide coating is formed on the surface of a substrate by chemical vapor deposition using inorganic tantalum halides and olefins. The present invention can effectively enable the substrate to obtain excellent high temperature resistance, corrosion resistance, and friction resistance, and at the same time has low reaction temperature and fast deposition speed, is more suitable for industrial production, and can effectively control the overflow of impurity components in the substrate, improve surface finish, and improve the aesthetics of the product, and realize large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic coating materials, and in particular relates to a tantalum carbide coating product and a preparation method thereof. Background Art

[0002] Tantalum carbide is a ceramic material with superconductivity and golden appearance. It has the advantages of high hardness (2100HV0.05), high melting point (3880℃), corrosion resistance and non-stickiness. It is an emerging ceramic material in recent years. Powdered tantalum carbide is widely used in the smelting process of special alloys. Tantalum carbide ceramics have broad application prospects in semiconductors, chemical industry, metallurgy, mold processing, aerospace, nuclear industry and other fields. It is an excellent shielding and wear-resistant material. However, its poor ductility, fragility and high processing cost restrict its widespread use.

[0003] Tantalum carbide materials are generally difficult to process and shape using machining processes due to their high melting point, high hardness, and poor ductility. The commonly used hot pressing sintering method is difficult to achieve dense and pore-free. Therefore, the preparation of tantalum carbide coating products using Chemical Vapor Deposition (CVD) has great significance and broad application prospects.

[0004] CVD refers to a gas phase reaction at high temperature, for example, the thermal decomposition of metal halides, organometallic compounds, etc., reduction or chemical reaction of their mixed gases at high temperature to precipitate inorganic materials such as metals, oxides, and carbides. This technology is not only used for coatings of heat-resistant materials, but also for the preparation of fiber-reinforced composite materials and the refining of high-purity metals. It is an advanced technical field with a wide range of applications. Chemical vapor deposition technology is a process in which gaseous substances react chemically on solids to produce solid deposits. It generally includes three steps: ① forming volatile substances; ② transferring the above substances to the deposition area; ③ producing chemical reactions on solids and producing solid substances. The most basic chemical vapor deposition process includes energy transfer, material transfer, etc.

[0005] Due to the large difference in thermal expansion coefficients between tantalum carbide coatings and substrates, especially carbon materials, cracks are prone to occur during the preparation process, and it is difficult to prepare high-quality tantalum carbide coatings. Therefore, the common practice is to use a carbon matrix (such as graphite) as a carbon source, first deposit tantalum, and then react with the carbon element on the surface of the carbon matrix (such as graphite) to form a tantalum carbide coating on the surface of the carbon matrix. This method uses the carbon on the surface of the carbon matrix as a carbon source, that is, the matrix itself is also part of the reactant. First, the deposition thickness cannot meet the use requirements, and second, it cannot be deposited on the surface of non-carbon-based materials. Summary of the invention

[0006] The present invention aims at the shortcomings of existing tantalum carbide coated products, uses a chemical vapor deposition method to prepare a tantalum carbide coating on the surface of a substrate, and provides a method for preparing a tantalum carbide coated product with corrosion resistance, wear resistance, high bonding strength and good appearance quality.

[0007] In order to achieve the above object, the present invention provides a method for preparing a tantalum carbide coated product, comprising the following steps:

[0008] ① Heating step, placing the substrate in a reaction chamber, evacuating the reaction chamber, and heating under the protection of an inert gas, wherein the heating temperature is 550-750° C.;

[0009] ② Deposition step, after the heating step, a mixed gas of tantalum pentachloride or tantalum pentafluoride gas, hydrogen, and mixed olefins is introduced into the reaction chamber, and heated for a certain period of time at a pressure of 5000Pa to 10000Pa to deposit a tantalum carbide coating on the surface of the substrate;

[0010] ③ Cooling step, after the above steps, cooling the tantalum carbide coating product to room temperature;

[0011] ④Cleaning step: after cooling to room temperature, take out the product and clean it with acetone.

[0012] Furthermore, the gasification temperature of the tantalum pentachloride or tantalum pentafluoride is 300-500°C.

[0013] Furthermore, the mixed olefin is a mixture of ethylene and propylene. Preferably, the volume ratio of ethylene to propylene is 1:1-2.

[0014] Furthermore, the volume ratio of the tantalum pentachloride or tantalum pentafluoride gas to the mixed olefins is 1:1-10, and the volume ratio of the tantalum pentachloride or tantalum pentafluoride gas to hydrogen is 1:1-5.

[0015] Preferably, the flow rate of the tantalum pentachloride or tantalum pentafluoride gas is 2-6 SLM, the flow rate of the mixed olefin gas is 2-60 SLM, and the flow rate of the hydrogen is 2-30 SLM.

[0016] Preferably, the tantalum pentachloride or tantalum pentafluoride gas is introduced into the reaction chamber via a carrier gas, and the carrier gas is argon; the volume ratio of the tantalum pentachloride or tantalum pentafluoride gas to the carrier gas is 1:1-4.

[0017] Preferably, the reaction chamber is an alumina reaction chamber.

[0018] Preferably, the heating step further includes pretreatment of the substrate: the surface of the substrate to be deposited is cleaned with distilled water to remove dirt, and then dried at 150° C. to 200° C. for 8 to 15 hours until it is completely dried.

[0019] Preferably, the substrate may be a metal, or a carbon material, or a high temperature resistant material such as ceramics and quartz.

[0020] Beneficial effects: The present invention uses tantalum halide, hydrogen and mixed olefins as raw materials and produces high-purity tantalum carbide coating materials through a chemical vapor deposition method, which effectively solves the drawbacks of existing tantalum carbide coating products, greatly improves production efficiency and reduces production costs.

[0021] (1) The present invention has a low reaction temperature and a fast deposition rate, and is more suitable for large-scale industrial production.

[0022] (2) The present invention uses mixed olefin gas, which has the greatest advantages of low reaction temperature, fast reaction rate and high safety factor in the production process. On the other hand, the use of mixed olefins can reduce the amount of residual carbon in the reaction.

[0023] (3) The tantalum carbide coating produced by this method has high purity and is free of impurities.

[0024] (4) The tantalum carbide coating prepared by the present invention effectively isolates the substrate from the external environment and can effectively protect the substrate.

[0025] (5) A corrosion-resistant and wear-resistant tantalum carbide isolation coating is prepared on the surface of the substrate by chemical vapor deposition. The thickness of the coating can be adjusted according to the actual product needs and can reach the millimeter level. This also shows that the coating product prepared by the present invention has strong bonding strength.

[0026] (6) The present invention heats and vaporizes tantalum halide and reacts with low-level hydrocarbons to directly produce tantalum carbide coating. The substrate itself does not participate in the chemical reaction, so the material requirements for the substrate are relatively loose, as long as it can withstand high temperatures. In addition to carbon materials (graphite, carbon / carbon, etc.), the coating can also be deposited on the surface of materials such as corundum, high-temperature alloys, and quartz. There are no requirements for the shape of the substrate, and it can be deposited on various special-shaped surfaces with good uniformity and dense structure. However, the prior art requires that the graphite substrate also participate in the carbonization reaction. This method cannot be deposited on the surface of non-carbon-based materials, and the deposition thickness is also incomparable to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A cross-sectional view of the tantalum carbide coating prepared in Example 1;

[0028] Figure 2 This is a cross-sectional view of the tantalum carbide coating of Example 2 (not polished);

[0029] Figure 3 This is a cross-sectional view of the tantalum carbide coating of Example 1;

[0030] Figure 4 This is a surface morphology of the tantalum carbide coating of Example 1;

[0031] Figure 5 This is a surface morphology of the tantalum carbide coating of Example 2;

[0032] Figure 6 is the Raman spectrum of the tantalum carbide coating in the embodiment;

[0033] Figure 7 The XRD spectrum of the tantalum carbide coating in the embodiment;

[0034] Figure 8 This is a metallographic photograph of the tantalum carbide coating in the embodiment;

[0035] Fig. 9 This is a schematic diagram of the chemical vapor deposition equipment system structure used in the present invention. DETAILED DESCRIPTION

[0036] Specifically described by some embodiments in order to fully understand the present invention. But the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0037] The present invention discloses a tantalum carbide coating product and a preparation method thereof. Chemical vapor deposition is a complex process, which includes the thermodynamics of chemical reactions, the kinetics of reactions, and multiple processes such as heat transfer and mass transfer. On the one hand, the chemical reaction must be controlled to occur in the reaction chamber, and on the other hand, the product must form a crystal nucleus and grow on the surface of the substrate. In other words, there is a possibility of chemical reaction between chemical substances, but there is no guarantee that the reaction process will occur efficiently, and it is necessary to continuously optimize the process parameters through multiple tests. Tantalum halides provide a convenient source of tantalum compounds for depositing tantalum carbide, especially tantalum pentahalide (TaX5), where X represents the halogen fluorine (F) and chlorine (Cl). The chemical reaction equation is as follows:

[0038] 2TaCl5+C2H4+3H2——2TaC+10HCl

[0039] 6TaCl5+2C3H6+9H2——6TaC+30HCl

[0040] The carbon source gas used in the traditional CVD process for depositing tantalum carbide is methane or propane. Alkanes have good stability and lower chemical reactivity than alkenes and alkynes. The reaction temperature of alkanes is high, side reactions will occur, and there are high requirements for equipment, and the reaction rate is also slow. Alkynes have the highest reactivity, the reaction temperature is very low, the coating deposition rate is also very fast, and they have extremely high production efficiency. The reaction temperature is low and the equipment requirements are also low. However, alkynes are prone to explosive cracking, which affects production safety. In addition, alkynes will undergo polymerization reactions, which have high quality requirements for control equipment and personnel.

[0041] Combining the above two points, the use of olefins has low production costs, high production efficiency and greatly improved safety.

[0042] A method for preparing a tantalum carbide coated product comprises the following steps:

[0043] (1) flushing and evacuating the vapor deposition equipment and all pipelines with an inert gas, wherein the inert gas is argon;

[0044] (2) Cleaning and decontaminating the green body to be deposited, drying it and placing it in a reaction chamber;

[0045] (3) Exhausting non-reactive gases and impurities that enter the vapor deposition equipment during the process of placing the green body;

[0046] (4) After checking that the vapor deposition equipment is sealed intact, the vacuum degree in the vapor deposition equipment is controlled to 5000-10000 Pa by a vacuum pump, and the temperature in the reaction chamber is heated to 550-750° C.;

[0047] (5) placing tantalum pentachloride or tantalum pentafluoride in a vaporization chamber and heating it to 300-500° C. to vaporize it, and passing the vaporized tantalum pentachloride or tantalum pentafluoride gas into a gas mixing tank at a gas flow rate of 2-6 SLM. At the same time, passing hydrogen and mixed olefins into the gas mixing tank at a hydrogen flow rate of 2-30 SLM and a mixed olefin gas flow rate of 2-60 SLM. After the three gases are fully mixed in the gas mixing tank, they are passed into a reaction chamber to perform a chemical vapor deposition reaction on the blank, and the reaction is performed for 1-20 hours to form a tantalum carbide coating of 30-600 μm on the surface of the substrate;

[0048] (6) Disconnect the heating power supply, stop heating, and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon gas. After the reaction chamber is filled to normal pressure, stop introducing argon gas, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coating material.

[0049] Among them, the chemical vapor deposition equipment includes a vaporization chamber and a reaction chamber. Figure 1As shown, the chemical vapor deposition equipment 1 has a reaction chamber 11, and the deposited workpiece 12 (such as a blank) is placed in the reaction chamber 11. The reaction chamber 11 is provided with two vents, one of which is connected to the air inlet pipe 13, and the other is connected to the vacuum pipe 14. The reaction chamber 11 is also provided with a heating device (not shown in the figure) that can heat the reaction chamber, and the outer end of the vacuum pipe 14 is connected to the vacuum pump 17. The air inlet pipe 13 is connected to a mixing tank 16, and the mixing tank 16 is connected to at least one ventilation pipe 161. In this embodiment, two are provided to respectively introduce reducing gas and inert argon gas from the ventilation pipe 161. The mixing tank 16 is connected to a vaporization chamber 15, and the vaporization chamber 15 can heat and vaporize the initial metal halide. The vaporized metal halide gas enters the mixing tank 16 and is fully mixed with other gases. The flow rate of the reaction gas is adjusted by the gas control device 18.

[0050] In the vaporization chamber, solid reactants such as tantalum chloride or other tantalum halides are vaporized by heat energy to become gaseous. The gaseous reactants react in the reaction chamber to convert the tantalum halides into a tantalum deposit layer.

[0051] The reaction chamber for vapor deposition uses an alumina reaction chamber. Compared with commonly used reaction chambers such as stainless steel reaction chambers, due to the high corrosivity of reactants and product gases, the stainless steel reaction chamber is corroded and cannot guarantee long-term stable operation. The alumina reaction chamber used in the present invention can guarantee long-term stable operation and is the best choice.

[0052] The purpose of steps (1) to (3) is to increase the bonding strength between the coating or composite material and the blank, and to perform pretreatment before chemical vapor deposition.

[0053] In step (4), the temperature of the reaction chamber needs to be high to ensure that the tantalum-chlorine bond or tantalum-fluorine bond in tantalum pentachloride or tantalum pentafluoride is completely dissociated, but the temperature of the reaction chamber should not be too high, otherwise the chemical deposition reaction will be carried out prematurely in other places before contacting the blank. The temperature affects the activation degree of the reactants. On the other hand, if the reaction room temperature is too high, it will cause an increase in side reactions and affect the purity of the coating. If the temperature is too low, the deposition rate will be slow or even no deposition will occur.

[0054] In step (5), the tantalum halide is vaporized by a carrier gas and then introduced into the reaction chamber. The carrier gas can be an inert gas that does not react chemically with the reactants, such as argon or neon or a mixture of argon and neon. In addition, tantalum carbide material can be deposited without a carrier gas. Controlling the direct delivery of tantalum halide vapor into the reaction chamber can be accomplished by heating the solid tantalum halide to a temperature range of about 300 to 500° C., and the temperature selection depends on the specific reactants. The selected temperature must be sufficient to vaporize the reactants to provide a vapor pressure for delivering the tantalum halide vapor into the reaction chamber. Therefore, a carrier gas is not required.

[0055] Tantalum carbide is prepared by using mixed olefin gas and tantalum pentachloride or tantalum pentafluoride gas. Compared with alkanes and alkynes, the biggest advantage of mixed olefin gas is the lower reaction temperature, faster reaction rate and higher safety factor in the production process. On the other hand, the use of mixed olefins can reduce the amount of residual carbon in the reaction. The reaction temperature, vacuum degree, reaction gas flow rate and ratio in the preparation process have a major impact on the speed of the deposition reaction and the structure and performance of the deposited layer. The ratio of mixed olefin gas to metal halide gas and carrier gas affects the concentration of the reactants. Too low or too high concentration of reactants affects the deposition efficiency. The reaction gas must have enough residence time on the surface of the blank to participate in the reaction. The deposition rate is controlled by the adsorption and desorption process between the reaction gas and the surface of the blank. When the gas flow rate increases, the source material participating in the reaction per unit time increases, which is conducive to the reaction in the direction of the product and the deposition rate increases. However, when the gas flow rate exceeds a certain range, some gas will not participate in the reaction and directly pass through the surface of the blank, causing waste. The process parameters in the chemical vapor deposition preparation process, such as reaction chamber temperature, equipment vacuum, reaction gas flow and ratio, metal halide vaporization temperature, deposition time and heat treatment process, all have an impact on the material properties of the product. They are mutually restrictive and complementary, and must be analyzed and adjusted in a unified manner when making process adjustments.

[0056] Preferably, the metal halide gas and the mixed olefins are fully mixed in a gas mixing tank and then introduced into a reaction chamber for chemical vapor deposition reaction. The mixed gas intake can make the deposition more uniform without excessive deposition or under-deposition.

[0057] In order to further explain the technical solution of the present invention, the present invention is described in detail by specific embodiments below. In industrial production, considering the economic cost, argon is used as an inert gas for protection in the embodiments, and it can also be extended to other inert gases that do not participate in chemical reactions. The following examples will help researchers in the field to further understand the present invention, but do not limit the present invention in any form. It should be pointed out that for ordinary technicians in the field, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0058] The following test equipment uses general equipment unless otherwise specified, which does not affect the final result. The electron microscope is Thermo Fisher Apero2, the element analyzer is Thermo Fisher Flash 2000, and the ICP is Shimadzu ICPE-9000.

[0059] Example 1

[0060] The chemical vapor deposition equipment is an aluminum oxide reaction chamber.

[0061] The materials and reagents used are as follows: high-purity graphite blank (30mm*40mm*50mm), high-purity mixed olefins (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), high-purity tantalum pentachloride (99.99%); the implementation steps are as follows:

[0062] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500Pa and maintained at a vacuum state of 500Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed intact, argon gas is introduced to fill the equipment to a normal pressure state, so that the argon gas fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon gas is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0063] (2) After the high-purity graphite blank is cleaned with distilled water and dried at 170° C. for 8 hours, it is placed in the reaction chamber to ensure that the surface of the blank to be deposited faces the outlet direction of the reaction gas and that the blanks do not overlap or block each other;

[0064] (3) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 15 minutes. After checking that the vapor deposition equipment is sealed intact, introduce argon gas to fill it to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the gas valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0065] (4) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 5000Pa through a vacuum pump, and heat the temperature in the reaction chamber to 550°C;

[0066] (5) placing tantalum pentachloride in a vaporization chamber and heating it to 300° C. to vaporize it, and passing the vaporized tantalum pentachloride gas into a gas mixing tank. At the same time, passing hydrogen, argon and mixed olefin gas into the gas mixing tank. The ratio of tantalum pentachloride, mixed olefin, hydrogen and argon is 1:2:2:3, and the flow rates are 2SLM, 4SLM, 4SLM and 6SLM respectively. After being fully mixed in the gas mixing tank, passing the gas into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 3 hours to prepare a tantalum carbide coated graphite material;

[0067] (6) Disconnect the heating power supply and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon gas. After the reaction chamber is filled to normal pressure, stop introducing argon gas, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0068] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 60μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested, and the peel strength was tested to be 25MPa, the graphite substrate was pulled apart, and the coating did not detach. Figure 1 and Figure 3 This is a cross-sectional view of the tantalum carbide coating of Example 1. Figure 4 This is the surface morphology of the tantalum carbide coating of Example 1. Figure 8 This is a metallographic picture, and there is no cracking. Figure 6 The Raman spectrum shows that the coating material is tantalum carbide. Through X-ray photoelectron spectroscopy (XPS) analysis of the tantalum carbide coating, it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, which is difficult to remove in the XPS test. Figure 7 is the XRD pattern of the prepared tantalum carbide coating.

[0069] Example 2

[0070] The chemical vapor deposition equipment is an aluminum oxide reaction chamber.

[0071] The materials and reagents used are as follows: high-purity graphite blank (100mm*50mm*20mm), high-purity mixed olefins (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), high-purity tantalum pentachloride (99.99%); the implementation steps are as follows:

[0072] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500Pa and maintained at a vacuum state of 500Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed intact, argon gas is introduced to fill the equipment to a normal pressure state, so that the argon gas fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon gas is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0073] (2) After the high-purity graphite blank is cleaned with distilled water and dried at 150° C. for 8 hours, it is placed in the reaction chamber to ensure that the surface of the blank to be deposited faces the outlet direction of the reaction gas and that the blanks do not overlap or block each other;

[0074] (3) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 15 minutes. After checking that the vapor deposition equipment is sealed intact, introduce argon gas to fill it to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the gas valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0075] (4) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 10000Pa by a vacuum pump, and heat the temperature in the reaction chamber to 750°C;

[0076] (5) placing tantalum pentachloride in a vaporization chamber and heating it to 500° C. to vaporize it, and passing the vaporized tantalum pentachloride gas into a gas mixing tank. At the same time, passing hydrogen, argon and mixed olefin gas into the gas mixing tank. The ratio of tantalum pentachloride, mixed olefin, hydrogen and argon is 1:4:6:6, and the flow rates are 2SLM, 8SLM, 12SLM and 12SLM respectively. After being fully mixed in the gas mixing tank, passing the mixture into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 10 hours to prepare a tantalum carbide coated graphite material.

[0077] (6) Disconnect the heating power supply and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon gas. After the reaction chamber is filled to normal pressure, stop introducing argon gas, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite carbon material.

[0078] The thickness of the tantalum carbide coating on the prepared tantalum carbide coated graphite material was detected using an electron microscope, and the detection results showed that the coating thickness was 65 μm. Figure 2 and Figure 5 The cross-sectional view and surface morphology of the tantalum carbide coating of Example 2 are shown respectively, and there is no cracking phenomenon. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and no other elements were found except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, which is difficult to remove in the XPS test.

[0079] Example 3

[0080] The chemical vapor deposition equipment is an aluminum oxide reaction chamber.

[0081] The materials and reagents used are as follows: high-purity graphite blank (30mm*30mm*30mm), high-purity mixed olefins (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), high-purity tantalum pentachloride (99.99%); the implementation steps are as follows:

[0082] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500Pa and maintained at a vacuum state of 500Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed intact, argon gas is introduced to fill the equipment to a normal pressure state, so that the argon gas fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon gas is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0083] (2) After the high-purity green body is cleaned with distilled water and dried at 150° C. for 8 hours, it is placed in the reaction chamber to ensure that the surface of the green body to be deposited faces the outlet direction of the reaction gas and that the green bodies do not overlap or block each other;

[0084] (3) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 15 minutes. After checking that the vapor deposition equipment is sealed intact, introduce argon gas to fill it to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the gas valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0085] (4) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 5000Pa through a vacuum pump, and heat the temperature in the reaction chamber to 550°C;

[0086] (5) placing tantalum pentachloride in a vaporization chamber and heating it to 500° C. to vaporize it, passing the vaporized tantalum pentachloride gas into a gas mixing tank, and at the same time, passing hydrogen, argon and mixed olefin gas into the gas mixing tank, wherein the ratio of tantalum pentachloride, mixed olefin, hydrogen and argon is 1:3:4:5, and the flow rates are 1SLM, 3SLM, 4SLM and 5SLM respectively, and after being fully mixed in the gas mixing tank, passing the gas into a reaction chamber to carry out a chemical vapor deposition reaction on the blank, and reacting for 10 hours; preparing a tantalum carbide coated graphite material;

[0087] (6) Disconnect the heating power supply and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0088] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 80μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was tested to be 24MPa, the graphite substrate was pulled apart, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was observed. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, which is difficult to remove in the XPS test.

[0089] Example 4

[0090] The chemical vapor deposition equipment is an aluminum oxide reaction chamber.

[0091] The materials and reagents used are as follows: high-purity carbon / carbon blank (30mm*30mm*30mm), high-purity mixed olefins (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), high-purity tantalum pentachloride (99.99%); the implementation steps are as follows:

[0092] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500Pa and maintained at a vacuum state of 500Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed intact, argon gas is introduced to fill the equipment to a normal pressure state, so that the argon gas fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon gas is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0093] (2) After the high-purity carbon / carbon blank is cleaned with distilled water and dried at 150° C. for 8 hours, it is placed in the reaction chamber to ensure that the surface of the blank to be deposited faces the outlet direction of the reaction gas and that the blanks do not overlap or block each other;

[0094] (3) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 15 minutes. After checking that the vapor deposition equipment is sealed intact, introduce argon gas to fill it to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the gas valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0095] (4) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 10000Pa by a vacuum pump, and heat the temperature in the reaction chamber to 750°C;

[0096] (5) placing tantalum pentachloride in a vaporization chamber and heating it to 500° C. to vaporize it, and passing the vaporized tantalum pentachloride gas into a gas mixing tank. At the same time, passing hydrogen, argon and mixed olefin gas into the gas mixing tank. The ratio of tantalum pentachloride, mixed olefin, hydrogen and argon is 1:3:4:4, and the flow rates are 1SLM, 3SLM, 4SLM and 4SLM respectively. After being fully mixed in the gas mixing tank, passing the mixture into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 10 hours to prepare a tantalum carbide coated carbon / carbon material;

[0097] (6) Disconnect the heating power supply and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon gas. After the reaction chamber is filled to normal pressure, stop introducing argon gas, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated carbon / carbon material.

[0098] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated carbon / carbon material was tested using an electron microscope, and the test results showed that the coating thickness was 77μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was tested to be 125MPa, the upper surface of the carbon / carbon substrate was peeled off, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was observed. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, which is difficult to remove in the XPS test.

[0099] Example 5

[0100] The chemical vapor deposition equipment is an aluminum oxide reaction chamber.

[0101] The materials and reagents used are as follows: high-purity graphite blank (30mm*30mm*30mm), high-purity mixed olefins (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), high-purity tantalum pentafluoride (99.99%); the implementation steps are as follows:

[0102] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500Pa and maintained at a vacuum state of 500Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed intact, argon gas is introduced to fill the equipment to a normal pressure state, so that the argon gas fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon gas is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0103] (2) After the high-purity green body is cleaned with distilled water and dried at 150° C. for 8 hours, it is placed in the reaction chamber to ensure that the surface of the green body to be deposited faces the outlet direction of the reaction gas and that the green bodies do not overlap or block each other;

[0104] (3) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 15 minutes. After checking that the vapor deposition equipment is sealed intact, introduce argon gas to fill it to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the gas valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0105] (4) Evacuate to 1000Pa vacuum state and maintain 1000Pa vacuum state for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 5000Pa by using a vacuum pump, and heat the temperature in the reaction chamber to 750°C;

[0106] (5) placing tantalum pentafluoride in a vaporization chamber and heating it to 500° C. to vaporize it, and passing the vaporized tantalum pentachloride gas into a gas mixing tank. At the same time, passing hydrogen, argon and mixed olefin gas into the gas mixing tank. The ratio of tantalum pentachloride, mixed olefin, hydrogen and argon is 1:1:1:1, and the flow rates are 1SLM, 1SLM, 1SLM and 1SLM respectively. After being fully mixed in the gas mixing tank, passing the gas into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 8 hours to prepare a tantalum carbide coated graphite material.

[0107] (6) Disconnect the heating power supply and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0108] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 23μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was tested to be 25MPa, the graphite substrate was broken, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was found. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, which is difficult to remove in the XPS test.

[0109] Example 6

[0110] The chemical vapor deposition equipment is an aluminum oxide reaction chamber.

[0111] The materials and reagents used are as follows: high-purity graphite blank (30mm*30mm*30mm), high-purity mixed olefins (99.999%), high-purity hydrogen (99.999%), high-purity argon (99.999%), high-purity tantalum pentafluoride (99.99%); the implementation steps are as follows:

[0112] (1) The chemical vapor deposition equipment is evacuated to a vacuum state of 500Pa and maintained at a vacuum state of 500Pa for 15 minutes. After checking that the chemical vapor deposition equipment is sealed intact, argon gas is introduced to fill the equipment to a normal pressure state, so that the argon gas fills the reaction chamber and all vacuum pipes. The gas valve is opened to evacuate the equipment, and argon gas is continued to be introduced for 10 minutes. The exhaust valve is closed. Through the above steps, various gases and impurities remaining in the chemical vapor deposition equipment are exhausted.

[0113] (2) After the high-purity green body is cleaned with distilled water and dried at 150° C. for 8 hours, it is placed in the reaction chamber to ensure that the surface of the green body to be deposited faces the outlet direction of the reaction gas and that the green bodies do not overlap or block each other;

[0114] (3) Evacuate to a vacuum state of 1000Pa and maintain the vacuum state of 1000Pa for 15 minutes. After checking that the vapor deposition equipment is sealed intact, introduce argon gas to fill it to normal pressure, so that the argon gas fills the reaction chamber and all vacuum pipes. Open the gas valve to evacuate, continue to introduce argon gas for 15 minutes, and close the exhaust valve. Through the above steps, various gases and impurities that enter the vapor deposition equipment during the placement of the blank are exhausted;

[0115] (4) Evacuate to 1000Pa vacuum state and maintain 1000Pa vacuum state for 10 minutes. After checking that the vapor deposition equipment is sealed intact, control the vacuum degree in the vapor deposition equipment to 5000Pa by using a vacuum pump, and heat the temperature in the reaction chamber to 750°C;

[0116] (5) placing tantalum pentafluoride in a vaporization chamber and heating it to 500° C. to vaporize it, and passing the vaporized tantalum pentachloride gas into a gas mixing tank. At the same time, passing hydrogen, argon and mixed olefin gas into the gas mixing tank. The ratio of tantalum pentachloride, mixed olefin, hydrogen and argon is 1:3:4:5, and the flow rates are 1SLM, 3SLM, 4SLM and 5SLM respectively. After being fully mixed in the gas mixing tank, passing the gas into a reaction chamber to carry out a chemical vapor deposition reaction on the blank for 8 hours to prepare a tantalum carbide coated graphite material;

[0117] (6) Disconnect the heating power supply and allow the reaction chamber to cool down naturally; when the temperature in the reaction chamber drops below 60°C, turn off the vacuum pump and continue to introduce argon. After the reaction chamber is filled to normal pressure, stop introducing argon, open the exhaust valve, open the reaction chamber, and take out the prepared tantalum carbide coated graphite material.

[0118] The thickness of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested using an electron microscope, and the test results showed that the coating thickness was 91μm. According to the ISO 4624-2016 coating adhesion test standard, the adhesion of the tantalum carbide coating of the prepared tantalum carbide coated graphite material was tested. The peel strength was tested to be 23MPa, the graphite substrate was broken, and the coating did not detach. The surface morphology of the coating was observed using a scanning electron microscope and no cracking was found. The tantalum carbide coating was analyzed by X-ray photoelectron spectroscopy (XPS), and it was determined that there were no other elements except Ta, C, and O. The oxygen element comes from the oxygen and carbon dioxide adsorbed by the sample in the atmosphere, which is difficult to remove in the XPS test.

[0119] The above embodiments and drawings do not limit the product form and style of the present invention. Any appropriate changes or modifications made by ordinary technicians in the relevant technical field, such as changes in parameters such as reaction temperature, vaporization temperature, gas flow rate, etc., should be deemed to be within the patent scope of the present invention.

Claims

1. A method for preparing a tantalum carbide coated product, using inorganic tantalum halide and olefin for chemical vapor deposition, characterized in that: The following steps are involved: ① Heating step, placing the substrate in a reaction chamber, evacuating the reaction chamber, and heating under the protection of an inert gas, wherein the heating temperature is 550 to 750° C.; ② A deposition step, after the heating step, introducing tantalum pentachloride or tantalum pentafluoride gas, hydrogen, and mixed olefins into a reaction chamber, maintaining the heating temperature at 550° C. at a pressure of 5000 Pa to 10000 Pa, and depositing a tantalum carbide coating on the surface of the substrate; the mixed olefin is a mixture of ethylene and propylene; the volume ratio of ethylene to propylene is 1:1 to 2; the volume ratio of tantalum pentachloride or tantalum pentafluoride gas to the mixed olefin is 1:1 to 10; ③ Cooling step: after the deposition step, cooling the tantalum carbide coating product to room temperature.

2. The method for preparing a tantalum carbide coating product according to claim 1, characterized in that: The gasification temperature of the tantalum pentachloride or tantalum pentafluoride is 300-550°C.

3. The method for preparing a tantalum carbide coating product according to claim 1, characterized in that: The volume ratio of the tantalum pentachloride or tantalum pentafluoride gas to the hydrogen gas is 1:1-5.

4. The method for preparing a tantalum carbide coating product according to claim 1, characterized in that: The flow rate of the tantalum pentachloride or tantalum pentafluoride gas is 2-6 SLM, the flow rate of the mixed olefin gas is 2-60 SLM, and the flow rate of the hydrogen gas is 2-30 SLM.

5. The method for preparing a tantalum carbide coating product according to claim 1, characterized in that: The tantalum pentachloride or tantalum pentafluoride gas is introduced into the reaction chamber by a carrier gas, and the carrier gas is argon gas.

6. The method for preparing a tantalum carbide coating product according to claim 5, characterized in that: The volume ratio of the tantalum pentachloride or tantalum pentafluoride gas to the carrier gas is 1:1-4.

7. The method for preparing a tantalum carbide coated product according to claim 1, characterized in that: The reaction chamber is an alumina reaction chamber.

8. The method for preparing a tantalum carbide coating product according to claim 1, characterized in that: The substrate includes at least one of metal, carbon material, ceramic or quartz.

Citation Information

Patent Citations

  • NMOS metal gate materials, manufacturing methods, and equipment using CVD and ALD processes with metal based precursors

    CN102918636A

  • Tantalum Carbide-Coated Carbon Material and Production Method Thereof

    US20120040172A1